Peran Pemerintah Dalam Mewujudkan Smart City Di Kota Tanjungpinang - Nur Aida Irsyada; Sella Oktapatika (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2023)
Smart City has become an important goal in urban development throughout the world, including in Tanjungpinang City. The government has a crucial role in realizing this Smart City vision. This research aims to understand the role of the government in achieving transformation towards a Smart City in Tanjungpinang City, as well as its impact on public services and the quality of life of the community. This study uses a qualitative approach with in-depth interviews and document analysis as data collection methods. The research results show that the Tanjungpinang City government has played an important role in realizing a Smart City through various initiatives, such as the use of information technology, more efficient public services, better data management, and development of supporting infrastructure. The impact of this government effort is to increase accessibility, security and quality of life for the community. However, there are still several challenges that need to be overcome, including the public's lack of understanding about Smart Cities, the sustainability of Smart City projects, and the protection of personal data. Therefore, the government needs to continue to act as a facilitator, service provider and regulator to ensure that the transformation towards a Smart City in Tanjungpinang City runs well. This research provides insight into the government's role in realizing a Smart City in Tanjungpinang City, as well as the challenges that must be faced. The results of this research can be a reference for the government and other stakeholders in efforts to achieve the goal of a more sustainable and inclusive Smart City.